2009
DOI: 10.1177/0165025408098021
|View full text |Cite
|
Sign up to set email alerts
|

Mean-level change and intraindividual variability in self-esteem and depression among high-risk children

Abstract: This study investigated mean-level changes and intraindividual variability of self-esteem among maltreated (n=142) and nonmaltreated (n=109) school-aged children from low-income families. Longitudinal factor analysis revealed higher temporal stability of self-esteem among maltreated children compared to nonmaltreated children. Cross-domain latent growth curve models indicated that nonmaltreated children showed higher initial levels and greater increases in self-esteem than maltreated children, and that the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 78 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…We also considered the possibility that changes in self-regulation and positive parenting (regardless of the levels) may be predictive of changes in adjustment outcomes. Therefore, we constructed the predictors of changes in child outcomes in two different ways: (1) average level defined as the mean of a given child's repeated measurements that represent reliable scores capturing stable, trait scores (e.g., Kim & Cicchetti, 2009; i.e., the averaging Time 1 and Time 2 scores of self-regulation and positive parenting to predict Time 2 outcome scores after controlling for Time 1 outcome scores ), and (2) change score between the two adjacent time points (i.e., subtracting Time 1 scores from Time 2 scores, thus positive scores indicate increases whereas negative scores indicate decreases). First, we tested whether changes in child maladjustment between Time 1 and Time 2 were predicted by main and interaction effects of self-regulation and positive parenting.…”
Section: Resultsmentioning
confidence: 99%
“…We also considered the possibility that changes in self-regulation and positive parenting (regardless of the levels) may be predictive of changes in adjustment outcomes. Therefore, we constructed the predictors of changes in child outcomes in two different ways: (1) average level defined as the mean of a given child's repeated measurements that represent reliable scores capturing stable, trait scores (e.g., Kim & Cicchetti, 2009; i.e., the averaging Time 1 and Time 2 scores of self-regulation and positive parenting to predict Time 2 outcome scores after controlling for Time 1 outcome scores ), and (2) change score between the two adjacent time points (i.e., subtracting Time 1 scores from Time 2 scores, thus positive scores indicate increases whereas negative scores indicate decreases). First, we tested whether changes in child maladjustment between Time 1 and Time 2 were predicted by main and interaction effects of self-regulation and positive parenting.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve a proper disaggregation of these two sources of variability, growth curve models (Bollen & Curran, ; Raudenbush & Bryk, ) in which individual‐specific intercepts (representing the mean initial level of GSE), slopes (representing linear or nonlinear evolution in GSE levels), and time‐specific residuals (representing state‐like deviations in GSE levels) are needed. The few studies relying on these methods confirmed these state‐trait interpretations in showing that time‐specific levels of GSE measured over a short follow‐up period (DeHart & Pelham, ; Zeigler‐Hill & Showers, ) or properly disaggregated time‐specific residuals estimated on longer developmental periods (Baldwin & Hoffmann, ; Kim & Cicchetti, ; Molloy, Ram, & Gest, ; Morin, Maïano, Marsh, et al., ) tended to fluctuate as a function of internal or external events occurring consecutively. Finally, implicit in these studies is the relative independence of GSE mean levels and indicators of instability (e.g., Kernis, , ).…”
Section: Substantive Issue 1—shape and Stability Of Self‐esteem Trajementioning
confidence: 91%
“…Another issue of importance is the study of youths' GSE trajectories is related to the repeated observation that GSE state‐like fluctuations are a more important predictor of adaptation than average levels of GSE (e.g., Kernis, , ; Kim & Cicchetti, ; Roberts & Monroe, , ; Zeigler‐Hill & Showers, ). However, most of these studies relied on intensive designs including multiple repeated measures taken over a relatively short period (e.g., 1–2 weeks), making it hard to generalize their results to longer time spans (e.g., Marsh, ; Ployhart & Vandenberg, ).…”
Section: Substantive Issue 1—shape and Stability Of Self‐esteem Trajementioning
confidence: 99%
“…To describe the extent and nature of fluctuations in self-esteem, two constructs have been introduced into the literature, specifically self-esteem instability (e.g., Kernis, 2005) and self-esteem contingency (e.g., Crocker & Wolfe, 2001). Although previous studies have investigated the relations of self-esteem instability and contingency with depression (e.g., Bos, Huijding, Muris, Vogel, & Biesheuvel, 2010;Butler, Hokanson, & Flynn, 1994;Kernis et al, 1998;Kim & Cicchetti, 2009;Meier, Semmer, & Hupfeld, 2009;Roberts, Shapiro, & Gamble, 1999;Sargent, Crocker, & Luhtanen, 2006), the results of these studies are highly inconsistent, SELF-ESTEEM AND DEPRESSIVE SYMPTOMS 4 as we will review in detail below. Moreover, we are not aware of any study that has pitted the effects of self-esteem level, instability, and contingency on depression against each other in the context of a single study.…”
mentioning
confidence: 99%